PERTUMBUHAN DAN HASIL TANAMAN PADI GOGO (Oryza sativa L.) PADA TANAH PODSOLIK (ULTISOL) YANG DIAPLIKASIKAN ZEOLIT FLY ASH - Nelvia Nelvia; Leony Putri Wijaya (Jurnal Agrotek Tropika, 2024)
The low productivity of upland rice on Podzolic (Ultisol) soil is caused by various constraints including low pH, the content of macronutrient N, P, K, Ca and Mg, BS and CEC were low, solubility and high Al saturation, high P fixation, delicate to erosion and water availability were low. Applied of zeolite synthesized from coal fly ash with high CEC is expected to overcome these constraints. The high negative charge on zeolite contributes to increasing soil absorption of nutrients provided or dissolved from soil minerals and decomposition of organic matter. The study was conducted experimentally using a completely randomized design, zeolite fly ash as the treatment consisting of 6 levels (0, 100, 150, 200, 250 and 300 kg ha-1) each repeated 3 times. The results showed that the application of zeolite fly ash dose 100-300 kg.ha-1 tends increased the plant height, filled grain number per panicle, the percentage of filled grain and 1000 grain weight compared without zeolite application and the highest increased showed in the number of maximum tillers and productive tillers and weight of milled dry grain per clump was obtained at a dose of 200 kg.ha-1 compared without zeolite is 45, 107 and 106% respectively.